A multi-layer-structured nickel-based electrode for high-performance binder-free asymmetric quasi-solid-state hybrid supercapacitors. (10th December 2022) - Lin, Yueming; Su, Siyu; Dai, Huimin; Xiang, Xiaoyan; Li, Panru; Zhu, Xiaohong
Abstract: A novel multi-layer-structured NiMn LDH/rGO/Ni(OH)2 @Ni foam (LRN@NF) is synthesized by a method combining hydrothermal and dip-coating processes, acting as an excellent electrode material for supercapacitors. The specific multi-layer structure and synergism of all the components boosts the electrochemical performance. Microstructural characterization illustrates the successful formation of the multi-layer structure and also demonstrates the important role of the incorporated graphene layers for the growth of NiMn LDH. The NiMn LDH/rGO/Ni(OH)2 @Ni foam shows a high specific capacity of 7.49C·cm −2 (specific capacitance of 14.40 F·cm −2 ) at 1 mA·cm −2 . Furthermore, the asymmetric quasi-solid-state hybrid supercapacitor (LRN@NF//AC; AC represents activated carbon) exhibits a high specific energy density of 0.23 mWh·cm −2 at a specific power density of 0.91 mW·cm −2 with a voltage window of 1.6 V, and 0.12 mWh·cm −2 of energy density can be maintained even at 64.04 mW·cm −2 . Therefore, the LRN@NF electrode is suggested to be a promising candidate for high-performance supercapacitors, and our research also demonstrates the feasibility and universality of the construction idea for excellent multi-layer-structured supercapacitor electrodes. Graphical abstract: Unlabelled Image Highlights: NiMn LDH/rGO/Ni(OH)2 @Ni foam possesses a novel multi-layer structure. It can prevent the agglomeration of each component and expose abundant active sites. An extremely high specific capacity of 7.49C·cm −2 is achieved at 1 mA·cm −2 . Assembled hybrid supercapacitor exhibits high energy and power densities.